Structure and Methodologies of Research in the Arnoldo Foà Archive - CARBONE, Rosa (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
The focus of this paper is the presentation and description of the Arnoldo Foà archive and its importance as the main documentary source for studying the contemporary actor: through the analysis of the sources contained therein, in fact, it was possible to conduct an in-depth study of theatrical career of Arnoldo Foà. The work is part of the Phd in Storia delle Arti e dello Spettacolo (History of Cinema, Music, Fine and Performing Arts) in Florence, a context in which I carry out a research dedicated to the artistic profile of Arnoldo Foà, protagonist of the theater from the second half of the twentieth century. Starting from the description of the archive in which the research was conducted, some significant examples are examined that can demonstrate how archival sources have managed to reveal unpublished and fundamental information for the study. Furthermore, the value and the high potential that the archive assumes as the main study tool for the performing arts are highlighted.